2017
DOI: 10.1111/aor.12989
|View full text |Cite
|
Sign up to set email alerts
|

Third Generation Ventricular Assist Device: Mid‐Term Outcomes of the HeartWare HVAD in Pediatric Patients

Abstract: The HeartWare HVAD is a small, third generation continuous flow pump that is intracorporeally placed for support of a failing ventricle in adult patients. This device is small in size when compared to other left ventricular assist devices and can therefore be used in smaller sized pediatric patients. We present our initial experience using the HVAD as a bridge to heart transplantation in the pediatric population. We performed a retrospective, single center, nonrandomized review of 17 pediatric patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Use of continuous flow VADs is increasing in the pediatric population, improving quality of life and decreasing wait list mortality (1,13,(17)(18)(19)(20)(21)(22)(23). Survival in this cohort was quite high and other groups have reported survival in pediatric patients comparable to the adult population supported by this device, including support of pediatric patients for over two years (21,23). However, pediatric patients pose unique challenges to VAD use, given the variability in indications and size of patients.…”
Section: Discussionmentioning
confidence: 78%
“…Use of continuous flow VADs is increasing in the pediatric population, improving quality of life and decreasing wait list mortality (1,13,(17)(18)(19)(20)(21)(22)(23). Survival in this cohort was quite high and other groups have reported survival in pediatric patients comparable to the adult population supported by this device, including support of pediatric patients for over two years (21,23). However, pediatric patients pose unique challenges to VAD use, given the variability in indications and size of patients.…”
Section: Discussionmentioning
confidence: 78%
“…As these devices are being used in children to prevent death while waiting a transplant, acceptable rates of adverse effects are not the only plausible reason. Significant advantage of CF‐LVADs is that the majority of patients can be discharged home and be able to return back to their daily life with their caregivers 12 . Low rates of adverse events and opportunity to live outside the hospital give these children a chance to avoid hospital acquired infections, have psychological support by their family, and have better physical condition provided by good rehabilitation, ultimately leading to a favorable health at the time of transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Mustafa Pac et al of the Turkey, Yuksek Ihtisas Hospital, Ankara, Turkey, reported on their initial experiences with the third generation continuous flow pump, HeartWare HVAD, as a bridge to heart transplantation in17 pediatric patients. A successful outcome was achieved in 13 patients.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%